Comparison of strong field approximation and quantitative rescattering model in generating of attosecond pulse. Issue 7 (January 2020) - Li, X Y; Fan, J; Wang, X L
Synopsis: In this paper, we want to investigate the differences between strong field approximation (SFA) and quantitative rescattering (QRS) model in macroscopically generating attosecond pulse. Our research shows that SFA can give comparable results to that from time-dependent Schrödinger equation (TDSE) in the cut-off range, but it encounters difficulties in reproducing the attosecond pulse of TDSE's in the low frequency range. However, the results from QRS agree well with that from TDSE method.